American Chemical Society album of new members, 1938-1939 - American Chemical Society (1938)
Photographic album containing approximately 440 black and white portraits of new members of the American Chemical Society for the years 1938-1939. The names and institutional affiliation of each individual are inscribed on the album page. The portraits are grouped by institutional affiliation, including members from Yale, Princeton, Cornell, MIT, Ohio State University, and Purdue.
Keywords: Chemists; American Chemical Society; Students; Learned institutions and societies